Kunsten at skrive revisionsrapporter: En beretning om forvaltningsrevisionens beretninger - Lise Justesen (Copenhagen Business School (CBS), 2008)
– This dissertation is about state performance auditing in Denmark – a practice that the National Audit Office of Denmark (NAOD) is mandated to undertake. My analysis of performance auditing takes as a starting point the fact that performance auditing is a kind of writing and that one immediate and obvious output of performance auditing consists of written reports. In a sense it could be argued that performance auditing is a particular kind of writing. However, not much research has paid attention to the question of how the writing of audit report is performed in concrete settings. What characterizes such processes? Does it follow certain rules? How are different actors involved? What kinds of effects follow from the writing and how, and to what extent, are the possible effects constrained by the particular kind of writing? The dividing line between the auditors as the writers, the auditee as the object of writing and the public as readers of the message conveyed by the report also seems to be questionable. In the dissertation, I show that in processes where it is difficult to determine in what sense a report is an output or an input and where these processes begin and end, the roles between writing and reading, active and passive may get blurred too.
hdl:10398/7046
Keywords: 650